Q. 94.7( 9 Votes )

What should

Answer :

Given:


p(x) = x2 – 5x + 4


3 is the zero of the resulting polynomial


Explanation:


p(3) = (3)2 – 5×3 + 4


p(3) = 9 – 15 + 4


p(3) = – 2


As – 2 is the remainder,


So 2 should be added to the given polynomial to get 3 as the zero of the resulting polynomial.


We can also verify the answer;


By adding 2 to the given polynomial we get;


P(x) = x2 – 5x + 4 + 2


P(x) = x2 – 5x + 6


P(3) = 9 – 15 + 6


P(3) = 15 – 15


P(3) = 0


Hence proved that 2 is the right answer to get 3 as the zero of resulting polynomial.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses